1978
DOI: 10.3181/00379727-158-40231
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Gram-Negative Bacterial Sepsis: Reevaluation of the Ability of Rough Mutant Antisera to Protect Mice

Abstract: 0.1 ml aliquots of serial dilutions of sera in physiologic saline, starting at 1: 10, were mixed with 0.1 ml of 1 x 108/ml suspensions of organisms previously washed 3X in physiologic saline; the mixtures were agitated 30 min on a Boerner type rotating machine at approximately 120 rotations per min at room temperature and agglutination read at 100 X magnification. Known negative and positive serum controls were always run concurrently. 482OO37-9727/78/ l583-O482$O 1 .OO/O

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

1981
1981
1995
1995

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 5 publications
1
31
0
Order By: Relevance
“…As with in-vitro phagocytosis studies, only antiserum raised against the K-antigen-bearing strain was protective against a challenge with live E. coli 075K. The lack of protection observed with 0 7 5 antiserum and with core-glycolipid antiserum (J5 antiserum) is in agreement with the results of others (Mullan et al, 1974;Ng et al, 1976;Greisman, Du Buy and Woodward, 1978;. However, in addition to capsular antibodies it has been reported that 0 antisera, core-glycolipid antisera and lipid A antiserum protect animals against challenge with E. coli (Wolberg and DeWitt, 1969;Galanos, Luderitz and Westphal, 1971;Kaijser et al, 1972;McCabe, 1972).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…As with in-vitro phagocytosis studies, only antiserum raised against the K-antigen-bearing strain was protective against a challenge with live E. coli 075K. The lack of protection observed with 0 7 5 antiserum and with core-glycolipid antiserum (J5 antiserum) is in agreement with the results of others (Mullan et al, 1974;Ng et al, 1976;Greisman, Du Buy and Woodward, 1978;. However, in addition to capsular antibodies it has been reported that 0 antisera, core-glycolipid antisera and lipid A antiserum protect animals against challenge with E. coli (Wolberg and DeWitt, 1969;Galanos, Luderitz and Westphal, 1971;Kaijser et al, 1972;McCabe, 1972).…”
Section: Discussionsupporting
confidence: 81%
“…These antibodies appear to act primarily as anti-endotoxic antibodies rather than as opsonins . In contrast, Ng et al, (1976) and Greisman, Du Buy and Woodward (1978) were unable to confirm the protective capacity of coreglycolipid antibodies against challenge with smooth gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Some investigators, however, were unable to obtain similar results [19][20][21][22][23][24][25][26][27][28]. For instance, Greisman and Johnston [27] found that mice inoculated with LPS from S. minnesota, Salmonella typhimurium, E. coli 0127, or E. coli 0111 were not protected by either of the two antisera to the J5 and Re mutants; the mortality among these mice was even greater than the mortality for mice that received only saline.…”
mentioning
confidence: 88%
“…Experimental work in animals (Ziegler et al, 1973 ;Braude et al, 1977) and clinical studies (Ziegler et al, 1982;Baumgartner et al, 1985) have shown the protective efficacy of such antisera. However, not all investigators have found consistent protection (Ng et al, 1976;Greisman et al, 1978;Van Dijk et al, 1981). The limitations of these studies have been that neither the precise molecular specificity nor the mechanism of protection have been fully defined.…”
Section: Introductionmentioning
confidence: 99%